Effect of molasses-urea-block (MUB) on dry matter intake, growth, reproductive performance and control of gastrointestinal nematode infection of grazing Menz ram lambs - Anindo, D.O.; Toe, F.; Tembely, S.; Mukasa-Mugerwa, E.; Lahlou-Kassi, A.; Sovani, S. (Elsevier, 1998)
The effect of urea-molasses feed-supplement blocks (MUB) on feed utilisation and the inclusion of anthelmintic medication into the blocks at strategic times to control nematode parasites was studied in lambs grazed on low quality tropical pasture. 120 Menz ram lambs of 5-7 months of age were divided into six groups for methods of treatment against internal parasites and urea molasses supplementation. The benzimidazole anthelminic febendazole was administered at the rate of 10 mg kg-1 liveweight as a drench or via medicated MuB. Animals grazed in two lots during the day and had access to grass hay in night pens ad libitum. Groups 1-3 comprised a non-supplemented (NOSUP) lot that only grazed while groups 4-6 consumed, in addition, an average of 80g per head per day of molasses-urea-block (SUPP) supplement. The MUB supplement was provided daily for nine months but medicated MUB was used only for strategic prophylactic treatment against nematodes. SUPP animals had higher daily DM intakes (568 (+ or -) 11 versus 532 (+ or -) 11 g DM per head per day, P<0.05) the advantage being greatest in the wet season when there was also a concomitant increase in herbage digestibility (P<0.001). SUPP animals were 4kg heavier (25.7 (+ or -) 0.5 versus 21.7 (+ or -) 0.5 kg, P<0.05) and had deposited more body reserves as judged by condition score (3.2 (+ or -) 0.1 versus 2.4 (+ or -) 0.1) after 6 months. The level of infection with endoparasites was lower in the dry than in the wet season. Medicated MUB was as efficient in treating against endoparasites as drenching. Similarly, the MUB supplement mitigated the effect of endoparasitism. Anthelmintic treatment did not improve testicular size or semen quality (P>0.05). Testicular growth increased faster during the first 3 months to highest values of 26.9 (+ or -) 0.3 and 25.3 (+ or -) 0.3 cm, respectively in SUPP and NOSUP animals (P<0.001) at 6 months. Semen quality improved with age and was better in SUPP than NOSUP males (P<0.05-P<0.001). It is concluded that MUB supplementation is a suitable method for supplementing the nutrition of grazing sheep in Ethiopia, and that MUB feeding can help alleviate the effect of endoparasitism.